2021
DOI: 10.37934/arfmts.86.2.107125
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Review on Mathematical Model for Convective Boundary Layer Flow

Abstract: Convection refers to the heat transfer that occurs between moving fluid and surface at a different temperature. Nowadays, there has been a great deal of interest in the convective boundary layer fluid flow problems. Despite its popularity, the review paper discussing the mathematical model for various fluid types regarding various geometry and boundary conditions has been observed to fall short. This review paper adopts a thematic review based on the mathematical model captured in published fluid flow proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…They found that the current is generated by the magnetic flux leaking inside the coils (the core of the transformer), and as a result of the oil coming into contact with the metal components, heat is transferred from the coils through the oil to the fins, so that the temperature of the hot spot, which does not have a fixed location, decreases. Kanafiah et al, [14] Analyzed articles that rely on the mathematical model to solve fluid flow problems using the thematic analysis program ATLAS.ti 8. This review paper adopts a review of only 50 articles on the topic as final articles from 2015 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the current is generated by the magnetic flux leaking inside the coils (the core of the transformer), and as a result of the oil coming into contact with the metal components, heat is transferred from the coils through the oil to the fins, so that the temperature of the hot spot, which does not have a fixed location, decreases. Kanafiah et al, [14] Analyzed articles that rely on the mathematical model to solve fluid flow problems using the thematic analysis program ATLAS.ti 8. This review paper adopts a review of only 50 articles on the topic as final articles from 2015 to 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Boundary conditions (BC) tell what the solutions of a model would be on the boundaries whereas surface geometry is the shape and condition of where the movement of analysed fluid is. There are four types of boundary conditions that are commonly used which are convective boundary condition (CBC), constant wall temperature (CWT), constant heat flux (CHF) and Newtonian Heating (NH) [7]. As for the geometry, flat plate, stretching/shrinking sheet, thin needle, rotating disk, vertical plate, sphere and horizontal circular cylinder are several of the geometries that interest the researchers which lead to an increasing number of publications every year [5].…”
Section: Introductionmentioning
confidence: 99%